Students’ sensemaking of self-other relations in Malaysian higher education institutions - Minah Harun; Syarizan Dalib; Norhafezah Yusof (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper discusses how Malaysian university students relate to the culture of others on campus based on sensemaking. More specifically, it articulates the sensemaking idea of self-other relations in which the individuals make sense of their experiences as they interact with others, how they view others around them and the others’ responses through socialising and their reflections of such acts. The paper is driven by the idea that to be effective global citizens, students should acquire intercultural competence by understanding their own social acts through interacting with others. Such competence is witnessed and enacted during interactions with culturally diverse others. The interactions are often taken for granted given that these acts are observable only among the interlocutors. The self-other understanding in interpersonal interaction requires people to understand not only what is said and meant in the process but also how to display proper conduct in performing the acts. Drawing from a series of focus group interviews with students in three Malaysian universities, the findings reveal that these students comprehended interaction with others using the language that reflects mindful acts, varied accommodating moves and appropriate cultural mannerisms. Such findings reflect the students’ meaning making of the interactions. It reveals the ways in which the students make sense of how the interactions influenced them and the conversant partners. The paper provides some implications including the need to embrace proper communication competencies in intercultural interactions in the campus and in other social or public spheres.